Long‐term effectiveness of recommended boosted protease inhibitor‐based antiretroviral therapy in Europe. Issue 5 (1st February 2018) - Santos, JR; Cozzi‐Lepri, A; Phillips, A; De Wit, S; Pedersen, C; Reiss, P; Blaxhult, A; Lazzarin, A; Sluzhynska, M; Orkin, C; Duvivier, C; Bogner, J; et al.
Abstract : Objectives: The aim of the study was to evaluate the long‐term response to antiretroviral treatment (ART) based on atazanavir/ritonavir (ATZ/r)‐, darunavir/ritonavir (DRV/r)‐, and lopinavir/ritonavir (LPV/r)‐containing regimens. Methods: Data were analysed for 5678 EuroSIDA‐enrolled patients starting a DRV/r‐, ATZ/r‐ or LPV/r‐containing regimen between 1 January 2000 and 30 June 2013. Separate analyses were performed for the following subgroups of patients: (1) ART‐naïve subjects (8%) at ritonavir‐boosted protease inhibitor (PI/r) initiation; (2) ART‐experienced individuals (44%) initiating the new PI/r with a viral load (VL) ≤500 HIV‐1 RNA copies/mL; and (3) ART‐experienced patients (48%) initiating the new PI/r with a VL >500 copies/mL. Virological failure (VF) was defined as two consecutive VL measurements >200 copies/mL ≥24 weeks after PI/r initiation. Kaplan–Meier and multivariable Cox models were used to compare risks of failure by PI/r‐based regimen. The main analysis was performed with intention‐to‐treat (ITT) ignoring treatment switches. Results: The time to VF favoured DRV/r over ATZ/r, and both were superior to LPV/r (log‐rank test; P < 0.02) in all analyses. Nevertheless, the risk of VF in ART‐naïve patients was similar regardless of the PI/r initiated after controlling for potential confounders. The risk of VF in both treatment‐experienced groups was lower for DRV/r than for ATZ/r, which, in turn, was lower than for LPV/r‐based ART. Conclusions: Although confounding by indication and calendar year cannot be completely ruled out, in ART‐experienced subjects the long‐term effectiveness of DRV/r‐containing regimens appears to be greater than that of ATZ/r and LPV/r.